Pengaruh Gaya Kepemimpinan Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Pendidikan Kabupaten Alor - Hermayanti Hermayanti; Junius Menase Sau Sabu (Peneliti.net, 2023)
The purpose of this study was to determine the effect of leadership style, work motivation and work environment on the performance of Alor District Education Office employees. This research is a qualitative research using primary data. The analytical tool used is multiple linear regression using an alpha of 5%. The sample in this study were all Civil Servants at the Alor District Education Office. Data analysis techniques consist of preliminary analysis including analysis of respondent identity descriptions, variable descriptions, validity tests, reliability tests and classical assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests and linearity tests, then proceed with advanced analysis consisting of t tests and F test and the coefficient of determination. The results of the study prove that leadership style (X1) has a positive and significant effect on employee performance (Y) with a significant value of 0.00 <0.05, work motivation (X2) has a positive and significant effect on employee performance (Y) with a significant value of 0.02 <0.05, work environment ( X3) has a positive and significant effect on employee performance (Y) with a significant value of 0.00 <0.05. Leadership style, work motivation and work environment have a positive and significant impact on employee performance as indicated by a significant value of 0.00 <0.05.